April 2022 Update to the Poverty and Inequality Platform (PIP) : What's New - Castaneda Aguilar, R. Andres; Dewina, Reno; Diaz-Bonilla, Carolina; Edochie, Ifeanyi N.; Fujs, Tony H. M. J.; Jolliffe, Dean; Lain, Jonathan; Lakner, Christoph; Ibarra, Gabriel Lara; Mahler, Daniel G.; Meyer, Moritz; Montes, Jose; et al. (World Bank, Washington, DC, 2022)
The April 2022 update to the newly launched Poverty and Inequality Platform (PIP) involves several changes to the data underlying the global poverty estimates. Some welfare aggregates have been changed for improved harmonization, and the CPI, national accounts, and population input data have been updated. This document explains these changes in detail and the reasoning behind them. Moreover, a large number of new country-years have been added, bringing the total number of surveys to more than 2,000. These include new harmonized surveys for countries in West Africa, new imputed poverty estimates for Nigeria, and recent 2020 household survey data for several countries. Global poverty estimates are now reported up to 2018 and earlier years have been revised.